Development Item-Based Questions World wall For Improving Science Learning Outcomes - Tiara Intan Cahyaningtyas; Nur Samsiyah; Sri Budyartati; Ridwan Musthofa; Agung Widyantoro; Krisma Lofitasari (International journal of technology and education research, 2026)
The quality of the questions produced by teachers is still very minimal and less interesting for students to use because they are only paper-based and only copied from existing books . Research purposes for develop an item question-based world wall to increase results Study in science subjects. Special purpose done for analyzing needs, designing product question-based worldwall, and describing results study science. Study this including in study development using the ADDIE development model. Subject study participants educate school-based class 4 Bulu 3 Madiun with a total of 15. Data collection techniques were carried out with questionnaires, validation, and tests. The instrument use sheet questionnaire needs a question-based word wall at the school base, sheet validation expert material and media, and questions test-based word wall. Research results produce questions that have been tested for validity, and reliability until you get 20 questions best and done validation by media experts and receiving materials the respective scores are 88% and 85% with the very worthy category. Response participants educated as many as 15 children and also received very good responses with give response of 90% and the results study increased from the initial average pre-test result of 51 to 89. Media questions word wall can be said feasible, interesting and effective increase results Study participant educate on the eyes Class IV science lesson on force and magnetism.